2013
DOI: 10.1021/ci3005786
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Properties of Ligands and Drugs in Protein Binding Sites: Tightly-Bound, Bridging Water Molecules and Their Effects and Consequences on Molecular Design Strategies

Abstract: Some water molecules in binding sites are important for intermolecular interactions and stability. The way binding site explicit water molecules are dealt with affects the diversity and nature of designed ligand chemical structures and properties. The strategies commonly employed frequently assume that a gain in binding affinity will be achieved by their targeting or neglect. However, in the present work, 2332 high-resolution X-ray crystal structures of hydrated and nonhydrated, drug and nondrug compounds in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 111 publications
1
63
0
1
Order By: Relevance
“…23 Instead, more approximate methods, such as Poisson-Boltzmann surface area techniques, 24 cellular automata models, 25 and grid cell theory 26 are typically employed. There is an unmet need for a technique that can rigorously and efficiently calculate the hydration free energy of protein binding sites using atomistic models, as such a method could facilitate investigations on the driving forces of biomolecular association, [27][28][29] help validate faster and more approximate techniques, as well as indicate forcefield inadequacies in projects where the length of simulation is not a constraint.…”
Section: Introductionmentioning
confidence: 99%
“…23 Instead, more approximate methods, such as Poisson-Boltzmann surface area techniques, 24 cellular automata models, 25 and grid cell theory 26 are typically employed. There is an unmet need for a technique that can rigorously and efficiently calculate the hydration free energy of protein binding sites using atomistic models, as such a method could facilitate investigations on the driving forces of biomolecular association, [27][28][29] help validate faster and more approximate techniques, as well as indicate forcefield inadequacies in projects where the length of simulation is not a constraint.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is no general rule to predict whether a water molecule will be retained within a protein-complex formation, or will be removed [22]. Trying to replace bridging waters led, also, to some unfavorable consequences in binding [244,245], highlighting how challenging is binding energy prediction, and the identification of the different contributions when water molecules are present.…”
Section: Modeling Waters Within the Active Sitementioning
confidence: 99%
“…It has been recently reported that compounds interacting with tightly bound bridging waters are as potent as those interacting only with binding site residues [22]. Ligands not stabilized by waters are generally bulkier, more hydrophobic, more complex, and have larger steric effects than those making interactions with structurally conserved water molecules within the target binding site.…”
Section: Wet or Dry Binding Sites?mentioning
confidence: 99%
See 2 more Smart Citations